Direct synthesis of ultra-thin large area transition metal dichalcogenides and their heterostructures on stretchable polymer surfaces. Issue 7 (3rd March 2016) - McConney, Michael E.; Glavin, Nicholas R.; Juhl, Abigail T.; Check, Michael H.; Durstock, Michael F.; Voevodin, Andrey A.; Shelton, Travis E.; Bultman, John E.; Hu, Jianjun; Jespersen, Michael L.; Gupta, Maneesh K.; Naguy, Rachel D.; et al.
Abstract: Abstract : A scalable approach for synthesis of ultra-thin (<10 nm) transition metal dichalcogenides (TMD) films on stretchable polymeric materials is presented. Specifically, magnetron sputtering from pure TMD targets, such as MoS2 and WS2, was used for growth of amorphous precursor films at room temperature on polydimethylsiloxane substrates. Stacks of different TMD films were grown upon each other and integrated with optically transparent insulating layers such as boron nitride. These precursor films were subsequently laser annealed to form high quality, few-layer crystalline TMDs. This combination of sputtering and laser annealing is commercially scalable and lends itself well to patterning. Analysis by Raman spectroscopy, scanning probe, optical, and transmission electron microscopy, and x-ray photoelectron spectroscopy confirm our assertions and illustrate annealing mechanisms. Electrical properties of simple devices built on flexible substrates are correlated to annealing processes. This new approach is a significant step toward commercial-scale stretchable 2D heterostructured nanoelectronic devices.